Computer analysis of high-speed PM BLDC motor properties - Krykowski, Krzysztof; Hetma czyk, Janusz; Ga uszkiewicz, Zbigniew; Miksiewicz, Roman (Compel, 2011)
Purpose - The purpose of this paper is to elaborate a method of computer analysis of high-speed motor with specific parameters and verifying the obtained results, i.e. computer models by experimental (laboratory) tests.Design methodology approach - In order to determine motor properties from the viewpoint of energy conversion, a model using FEM was worked out with the help of Maxwell software. To determine static and dynamic properties of both motor and drive, Matlab Simulink models were used; one of these models was a built-in (library) model, the other one was proposed by the authors.Findings - The new analysis method and model of high-speed motor have been carried out.Research limitations implications - The permanent magnet brushless direct current high-speed motor was the subject of the research. In the first part of the research, the properties of the motor were determined by using finite element method.Practical implications - The laboratory prototype can be a starting point in establishing the production of the high-speed motors with rotational speed in the range of 50,000-100,000 rpm.Social implications - At this moment, there are several possible application of the high-speed motor and it should be expected that other new applications can appear in near future after the start of the production.Originality value - The paper shows that the computer-based analysis method determines the motor properties accurately. It is also pointed out that a motor with half-open slots has advantageous properties. The new simulation model of high-speed motor has been carried out. This model allows taking into account some imperfections caused by slots and rectangular cross-section magnets.